Unspeakable: a game adaptation of MacEwan's Book of the Year design series "How to Pronounce Knife" - Tolentino, Kayla (My University, 2022)
Language has a significant part in the book How To Pronounce Knife. Many of the characters from the book encounter challenges in their everyday lives that have to do with language but still embrace who they are, and they don’t try to be what societal norms are. This ideal and raw characteristic of the characters from the books is what inspired this card game. Unspeakable is a card game that challenges players to guess words and phrases based on the book how to pronounce knife. It is perfect for people who read the book. The game involves acting phrases or words from the book provided by the other team. The objective is to have your team guess the answer without talking and using gestures alone. The game is easy to play anywhere, requires less preparation but needs a lot of imagination. It is created to learn how to communicate with others without using a single word and get rid of language barriers, just like how the characters in the book show so many ways to communicate, not just by language but also through gestures and connections. The packaging design reflects the lightness of the short stories and how ferocious the characters are. Vibrant colours are used to demonstrate the character’s rich experiences and to break how society describes immigrants’ lives as sad and tragic. The primary colours are red, white, and yellow to unify it with the book still. The unique, minimalistic, and joyful shapes mirror the book’s artful blend of simplicity and sophistication. The wordmark logo represents fold pages to indicate how the game is based on a compilation of short stories. There are 100 cards with words or phrases from the book, a sand timer, a score-pad, and a game guide inside the box. The cards are also colourful to keep the dynamic feeling from the packaging to the inside. The words are bolded and have a page number beneath so the players can still reference where the word or phrase came from in the book. Overall, the design makes the packaging dynamic and whimsical, which associates with the book’s general feel.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta.
Keywords: packaging design; game adaptation; MacEwan Book of the Year